Common Local and Systemic Side Effects of Sinovac Covid-19 Vaccine Among Children and Adult Participants - Imrana Ata, Aummara Rafique, Hira Ameer, Amna Fayyaz, Ariba Sidddiqui, Adnan Anwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Vaccination is one of the primary measures for halting the COVID-19 outbreak. Although there are several vaccines in use around the globe, little is known about the Sinovac vaccine's efficacy and side effects. Therefore, the purpose of this study was to investigate the reported side effects of the Sinovac vaccine in children and adult participants. Methodology: This was a multi-centered, cross-sectional study that was performed, using a non-probability sampling method. The study’s duration was about eight months, from March 1, 2022, to October 31, 2022 after taking approval. The study included 450 participants, including 225 children and 225 adults, who had either received the first or second dose of the Sinovac vaccination. Age, weight, height, and duration of diabetes and hypertension were documented as means and standard deviations. Frequencies and percentages were documented for demographic features. A chi-square test was used to determine the association between local and systemic side effects among children and adult participants. Results: The study findings showed that out of 450 participants, One hundred forty (62.2%) male participants and 85(37.8%) female participants were under the age of 18, and 163(72.4%) male participants and 62(27.6%) female participants were above the age of 18 years, with a significant difference observed among them (p=0.021). Following the first dose of the Sinovac vaccine, fever was the most frequently reported side effect in 123(54.7%) children and 81(36.0%) adult participants, with a substantial association noticed among them (p<0.001). Similarly, following the 2nd dose of the Sinovac vaccine, fever was the commonly reported side effect in 94(41.8%) children and 61(27.1%) adult participants, with a substantial association noticed among them (p=0.001). Conclusion: This study concluded that the most frequently reported side effect was fever in both children and adult participants following receiving the first and second doses of Sinovac vaccines. Moreover, pain and swelling at the injection site were the only local side effects observed. Additionally, the observed side effects were more pronounced after the first dose as compared to the second dose. Keywords: Sinovac vaccine, fever, pain, swelling injection site.